INGO Sebagai Agent of Aid: Peran dan Kontribusi Oxfam Internasional dalam Penyaluran Bantuan untuk Pengentasan Kemiskinan - Rasyidah, Resa (Global and Policy Journal of International Relations, 2014)
ABSTRACTInternational Non-Government Organizations (INGOs) is an important actor of the most influential in the distribution of foreign aid and global philanthropy. The role and contribution of INGOs has been increased post-Cold War 1991. INGOs have given a lot of help in distributing aid to development and poverty reduction in Medium Income Countries (MICs) and Low Income Countries (LICs). Therefore, the INGOs are often referred to as Agent of Aid. This paper is to describe how the role and contribution of INGOs as an Agent of Aid post-Cold War, with Oxfam as the case study especially its role and contribution to the alleviation of poverty.Keywords: INGOs, Agent of Aid, Role and Contribution, Oxfam, PovertyDOI:https://doi.org/10.33005/jgp.v2i01.1983